Violência e gênero: representações sociais de peritos médico-legais do IML/SE sobre a violência sexual - Araújo, Liliana Aragão de (2013)
Using sociological theories and based on theories of gender and social representations, whose main thesis is to analyze the social representations of forensic experts from the Forensic Institute of Sergipe - IML / SE, seeing if they reproduce asymmetrical relations between men and women regarding victims of sexual violence. Looking up then highlight the factors that can contribute to the strengthening of violence, with a view to protecting the rights of victims in cases of sexual coercion and violence. Therefore, this research is a qualitative, but not move away from quantitative data to build the profile of the victims of violence, the aggressor, and the phenomenon of forensic experts. Thus, we opted for a case study because it seeks to understand contemporary phenomena and real life, where you need a deeper analytical facts. Therefore, it was necessary to use three types of methodological tools: the documentary, interviews and non-participant observation. Thus, after reviewing the reports psychosocial visualize that victims are often young women, most adolescent aged 13 to 18 years and where crime occurs in men, usually in children or early teens. Their abusers are people the family environment: neighbors, fathers, stepfathers, uncles, cousins, grandparents, for this reason, the violence that occurs in space known by the victim: at home, at the abuser, or a family member. We also conducted six interviews were with these five men and one woman with, we can consider them as these professionals represent sexual violence. It was then realized that the forensic experts tend to be more technical, sometimes showing, sometimes certain degree of prejudice or stereotyping, as the expert forensic expertise exhibit more psychological aspects of the victims. Already on observations visualize how the service takes place the victim in this first contact at the reception of IML / SE until the completion of corpus delict exam. In observation of the test corpus delicti once again realize that men are more objective concentrating in the exam only, since women are more communicative environment which provides a lighter to the victim. It was concluded that there are still remnants of prejudices and sterotyping in serving victims, however I do not know if that plays in preparing the expert report, since I did not have access to this document, moreover, that the institution do not comply the amendment of legislation of sexual crimes. However, in meeting the victim was not perceived any kind of exposure of the victim or his family, and noted an improvement in the structure of IML / SE, particularly with regard to the technological area.